Spiritual Possession and the Role of Traditional Healers in Nepal - Acharya, Sandeep (Journal of Nepal Health Research Council, 2019)
Spiritual possession is a relatively common phenomenon, and occurs in many cultures around the world. It is a frequent claim in Nepal that illness is caused by spiritual possession, and ill people often seek out traditional healers for treatment. Traditional healers are often not medically trained, and this could have an adverse effect on a person’s health as serious illnesses may not be managed appropriately. However, there is perhaps a role that traditional healers can play in the management of patients. Keywords: Culture; Nepal; spirit possession; traditional medicine.